Study and Fabrication of Europium Picrate Triethylene Glycol Complex - Saleh, M.I.; Kusrini, E.; Mohd Sarjidan, M.A.; Abd Majid, Wan Haliza (Elsevier, 2011)
A mononuclear of Eu(NO3)(Pic)(H2O) 2(EO3)(Pic)Â·(0.73)H2O complex, where EO3 = trietraethylene glycol and Pic = picrate anion, shows a red emission when used as an active layer in a single layer of ITO/EO3-Eu-Pic/Al configuration. The crystal structure of the complex consists of Eu(NO3)(Pic)(H 2O)2(EO3)+ cation and Pic- anion. The Eu(III) ion is coordinated to the 10 oxygen atoms from one EO3 ligand, one Pic anion, one nitrate anion, and two water molecules. The complex is crystallized in triclinic with space group P-1. The hybrids in thin films I and II were prepared in the respective order solution concentrations of 15 and 20 mg/mL the emissive center. Comparing the photoluminescence (PL) and electroluminescence (EL) spectra, we can find that all emissions come from the characteristic transitions of the Eu(III) ion. The EL spectra of both thin films showed the occurrence of the most intense red-light emission around at 612 nm. Comparison of organic light-emitting device (OLED) current intensity characteristics as a function of voltage (I-V) show that the thin film I is better than those found for the thin film II. The thickness of the emitting layer is an important factor to control the current-voltage curve. The sharp and intense emission of the complex at low voltage indicates that the complex is a suitable and promising candidate for red-emitting materials. Â© 2010 Elsevier B.V. All rights reserved.